Når børn og unge pålægges sagsomkostninger i straffesager - Kasper Jørgensen; Emilie Thage; Annette Olesen (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract In Denmark, juveniles (aged 15-17) – like adults – are required to repay the Treasury for necessary expenses incurred in the processing of their criminal cases. However, data from the Danish National Police and the Danish Debt Collection Agency indicate that juveniles often lack the means to repay these debts and are therefore indebted as they enter adulthood. This article examines the psychological impact of debt on juveniles deprived of their liberty and the impact debt has on their ability to establish a ‘normal’ adult life. Linking the concept of ‘emerging adulthood’ to the literature on ‘debt as a risk factor’ provides a theoretical basis for the analysis and for the discussion of human rights. The article argues that neglecting the distinctive vulnerabilities of juveniles in the assessment of legal costs may obstruct their rehabilitation and violate their human rights.